The Effect of Adding Aluminium on the Performance of ZnO NRs/PANi in Their Application as Photoelectrochemical Water Splitting - Sari, Eprilia Trikusuma; Mufti, Nandang; Nadhira, Anissa Chairani Alfin; Wisodo, Hari; Diantoro, Markus (Journal of Mechanical Engineering Science and Technology (JMEST), 2023)
Photoelectrochemical (PEC) is a new renewable energy technology that converts H2O into hydrogen and oxygen gas with the help of sunlight. A photoelectrochemical cell device consists of three main components, one of which is the photoanode. One of the materials that can be used as a photoanode is ZnO which has good electrical properties and is non-toxic. Nanorods-structured ZnO has the advantage of being able to increase light absorption due to its high surface area. However, the resulting performance is still quite low. So it is necessary to make modifications to the photoanode, one of which is by adding aluminium material to ZnO NRs, which has the potential to increase the conductivity of PEC in the production of H2 and O2 in H2O. To overcome the loss of samples during testing, the thin film will be coated with conductive polymers such as polyaniline (PANi), which has high conductivity, can increase photoactive ability, and has good corrosion resistance. In this study, the performance of ZnO NRs/PANi against AZO NRs/PANi will be studied by adding aluminium. The ZnO nanorods were synthesized by Hydrothermal method, Aluminium was deposited on ZnO NRs by DC Magnetron Sputtering method, and PANi was synthesized by polymerization method. From the XRD characterization results, it can be concluded that the addition of aluminium to ZnO NRs/PANi causes an increase in crystallinity and peak shift. SEM characterization shows that the addition of Al to ZnO NRs/PANi causes the porosity value to increase. In addition, UV-Vis characterization showed that the addition of Al material to the ZnO NRs/PANi thin film resulted in a wider range of absorbance of the light spectrum. Then, Cyclic Voltammetry test shows that the addition of aluminium increases the efficiency of the photoelectrochemical.